Diversity and population connectivity of members of the family Eunicidae inhabiting deep-water corals in the North Atlantic - Carlota Gracia-Sancha; Nicolai Roterman; Michelle L. Taylor; Kerry L. Howell; Alex D. Rogers; Sofía Ruiz-Cano; Sergi Taboada (Molecular Phylogenetics and Evolution, 2026)

Effects of surgical implantation of electronic tags in fishes: a review and meta-analysis - Mitchell B. Shorgan; Graham D. Raby; Amber L. Fedus; Bradley E. Howell; Laura S. E. Haniford; Leah C. Howitt; Natalie V. Klinard; Jordan K. Matley; Jacob W. Brownscombe; Steven J. Cooke; Aaron T. Fisk (Reviews in Fish Biology and Fisheries, 2026)

Vascular contribution to cognitive impairment and dementia (VCID): proceedings of 2025 workshop of the Jackson Laboratory - Mehwish Anwer; Tetiana Poliakova; Ricardo D’Oliveira Albanus; Mohammad Iqbal H. Bhuiyan; Adam M. Brickman; Soumilee Chaudhuri; Leah Cuddy; Maxwell Eisenbaum; Kate Foley; Douglas B. Gould; Catherine Hall; Costantino Iadecola; et al. (Mammalian Genome, 2026)
The first Vascular Contributions to Cognitive Impairment and Dementia (VCID) Workshop, held on May12-16, 2025 at The Jackson Laboratory, provided scientific content and career development training in the latest developments in VCID and Alzheimer’s Disease (AD) and related dementia (ADRD). The Workshop aimed to foster interdisciplinary collaborations and empower the next generation of diverse scientists to advance ADRD research from mechanism to intervention. The meeting placed a strong emphasis on neurovascular pathology, its central role in ADRD pathogenesis, its modulation by both central and peripheral factors, and the critical need to dissect the mechanistic basis of VCID through experimental models. The workshop included talks from both faculty and trainees and was bookended by two keynote addresses by Drs. Donna Wilcock and Costantino Iadecola, leaders and pioneers in the VCID field. The second VCID workshop is planned for April 28-May 1, 2026, to be held at Washington University in St. Louis.

Parametric Sensitivities of a Nonsmooth Wilson-Cowan Model with a Comparison to its Smooth Counterpart - Cadi L. Howell; Peter Stechlinski (Mathematical Biosciences, 2026)

Preliminary Results of a Multistate Community Education Program, Capture the Flavor: Herbs and Spices - Allison Howell; Beverly Jackey; Cheryl Bush; Jennifer Dixon Cravens; Mona Habibi; Julie Buck; Theresa L. Serio; Laura Sant; Amy Robertson; Gina Crist; Deon Littles; Diane Oliver; et al. (Journal of Nutrition Education and Behavior, 2026)

A generalized linear mixed model approach to assess associations between Certified Food Protection Managers and inspection performance in Franklin County, Ohio - Allison Howell; Alexander Evans; Sarah Jensen; Nicole L. Arnold; Barbara Kowalcyk (Food Control, 2026)

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Navigating danger: Watercraft-related mortality of sea turtles in the United States Atlantic and Gulf coastal waters - Mariana M.P.B. Fuentes; Brian A. Stacy; Susan G. Barco; Robert A. DiGiovanni; Karen M. Dourdeville; Kimberly F. Durham; Mark Faherty; Sarah A. Finn; Allen M. Foley; Matthew H. Godfrey; Robert F. Hardy; Lyndsey N. Howell; et al. (Biological Conservation, 2025)

Elemental analysis by neutron activation analysis and synchrotron x-ray fluorescence microscopy of ocean plastics ingested by pelagic seabirds - Jennifer L. Lavers; Nicholas R. Howell; Alexander L. Bond; Daryl L. Howard; Martin D. de Jonge; Ljiljana Puskar; Richard B. Banati (Journal of Hazardous Materials, 2025)

Corrigendum to “Multiple-species resistance to avermectin/milbemycin anthelmintics on beef cattle farms in Georgia, USA” [Vet. Parasitol. 336 (2025) 110435] - Leonor Sicalo Gianechini; Kelsey L. Paras; Melissa M. George; Sue B. Howell; Bob Storey; Matthew J. Denwood; Ray M. Kaplan (Veterinary Parasitology, 2025)

Multiple-species resistance to avermectin anthelmintics on beef cattle farms in Georgia, USA - Leonor Sicalo Gianchini; Kelsey L. Paras; Melissa M. George; Sue B. Howell; Bob Storey; Matthew J. Denwood; Ray M. Kaplan (Veterinary Parasitology, 2025)

Co‐Existence Slows Diversification in Experimental Populations of E. coli and P. fluorescens - Gareth Howells; Aysha L. Sezmis; Christopher Blake; Michael J. McDonald (Environmental Microbiology, 2025)
Microbes grown in heterogeneous laboratory environments can rapidly diversify into multiple, coexisting variants. While the genetic and evolutionary mechanisms of laboratory adaptive radiations are well studied, how the presence of other species alters the outcomes of diversification is less well understood. To test the effect of co‐culture growth on the Pseudomonas fluorescens SBW25 adaptive radiation, Escherichia coli and P. fluorescens were cultured in monoculture and co‐culture for 8 weeks. In P. fluorescens monoculture, Wrinkly and Smooth Spreader types rapidly evolved and were maintained over 8 weeks, while E. coli monocultures evolved two colony types, a big and a small colony variant. In contrast, we found that in co‐culture, E. coli did not evolve small colony variants. Whole genome sequencing revealed the genetic basis of possible co‐culture specific adaptations in both E. coli and P. fluorescens . Altogether, our data support that the presence of multiple species changed the outcome of adaptive radiation.

Diverse and ecologically unique mesophotic coral ecosystems in the central Indian Ocean - C. Diaz; K. L. Howell; P. Hosegood; A. Bolton; N. L. Foster (Coral Reefs, 2024)
Research on Mesophotic Coral Ecosystems (MCEs; 30–150 m) has grown exponentially in the last few decades, highlighting their rich diversity and extensive distribution. However, they are still largely underexplored compared to shallow-water coral reefs and frequently remain under-protected and under-represented in marine spatial planning. One reason for the imbalance between the high ecological value of MCEs and the limited levels of protection may be that baseline data on MCEs are largely missing to date, yet are crucial to provide evidence-based information for management actions. Here, we present data on the alpha and beta diversity of the benthic communities within MCEs in the Chagos Archipelago, Indian Ocean. Using imagery collected from Remotely Operated Vehicle surveys, benthic invertebrate megafauna were surveyed along the entire depth gradient from shallow to lower mesophotic depths (15–160 m). The diversity of the benthic communities decreased with increasing depth, from shallow water to the lower mesophotic zone. Nevertheless, the deepest parts of MCEs in the Archipelago displayed higher species richness values than several other shallow subtropical regions. In addition, the benthic communities showed high dissimilarity along the depth gradient, indicating that the key driver of community composition change with depth is species turnover (species replacement), revealing the uniqueness of MCEs. This study presents novel findings on MCEs in the central Indian Ocean, demonstrating that they host a high and unique benthic diversity, and highlighting the need to protect these ecosystems to preserve the overall biodiversity of coral reefs.

Antibacterial activity of Au(I), Pt(II), and Ir(III) biotin conjugates prepared by the iClick reaction: influence of the metal coordination sphere on the biological activity - Dominik Moreth; Lars Stevens-Cullinane; Thomas W. Rees; Victoria V. L. Müller; Adrien Pasquier; Ok-Ryul Song; Scott Warchal; Michael Howell; Jeannine Hess; Ulrich Schatzschneider (JBIC Journal of Biological Inorganic Chemistry, 2024)

Naturally occurring radioactive materials in offshore infrastructure: Understanding formation and characteristics of baryte scale during decommissioning planning - Amy MacIntosh; Daniel T. Oldfield; Dioni I. Cendón; Andrew D. Langendam; Nicholas Howell; Daryl L. Howard; Tom Cresswell (Journal of Hazardous Materials, 2024)

Trajectories and tipping points of piñon–juniper woodlands after fire and thinning - Michala L. Phillips; Cara Lauria; Tova Spector; John B. Bradford; Catherine Gehring; Brooke B. Osborne; Armin Howell; Edmund E. Grote; Renee J. Rondeau; Gillian M. Trimber; Benjamin Robinson; Sasha C. Reed (Global Change Biology, 2024)
Piñon–juniper (PJ) woodlands are a dominant community type across the Intermountain West, comprising over a million acres and experiencing critical effects from increasing wildfire. Large PJ mortality and regeneration failure after catastrophic wildfire have elevated concerns about the long‐term viability of PJ woodlands. Thinning is increasingly used to safeguard forests from fire and in an attempt to increase climate resilience. We have only a limited understanding of how fire and thinning will affect the structure and function of PJ ecosystems. Here, we examined vegetation structure, microclimate conditions, and PJ regeneration dynamics following ~20 years post‐fire and thinning treatments. We found that burned areas had undergone a state shift that did not show signs of returning to their previous state. This shift was characterized by (1) distinct plant community composition dominated by grasses; (2) a lack of PJ recruitment; (3) a decrease in the sizes of interspaces in between plants; (4) lower abundance of late successional biological soil crusts; (5) lower mean and minimum daily soil moisture values; (6) lower minimum daily vapor pressure deficit; and (7) higher photosynthetically active radiation. Thinning created distinct plant communities and served as an intermediate between intact and burned communities. More intensive thinning decreased PJ recruitment and late successional biocrust cover. Our results indicate that fire has the potential to create drier and more stressful microsite conditions, and that, in the absence of active management following fire, there may be shifts to persistent ecological states dominated by grasses. Additionally, more intensive thinning had a larger impact on community structure and recruitment than less intensive thinning, suggesting that careful consideration of goals could help avoid unintended consequences. While our results indicate the vulnerability of PJ ecosystems to fire, they also highlight management actions that could be adapted to create conditions that promote PJ re‐establishment.

A risk assessment for the remote ocean: the case of the South East Atlantic - Holly J. Niner; Siân E. Rees; Giulia La Bianca; Kirsty A. McQuaid; Kerry L. Howell (Frontiers in Marine Science, 2024)
Degradation of the natural world and associated ecosystem services is attributed to a historical failure to include its ‘value’ in decision-making. Uncertainty in the quantification of the relationship between natural capital ‘assets’ that give rise to critical societal benefits and people is one reason for the omission of these values from natural resource management. As this uncertainty increases in marine systems and further still with distance from the coast, the connection between society and natural capital assets is less likely to be included adequately in decision-making. Natural capital assets of Areas Beyond National Jurisdiction (ABNJ), including those of the deep sea, are distant but are known to generate many benefits for society, from the diffuse and broad-scale benefits of climate regulation to the provision of wild fish for food. While our understanding of the precise relationships (the status of asset stocks, ecosystem functions and processes) that control the availability of ecosystem services and the flows of benefits is limited, this does not preclude opening a discourse on how these natural capital assets could best be managed to continue to benefit society. Here we apply a natural capital approach to the South East Atlantic ABNJ, one of the least scientifically understood regions of the planet, and develop a framework for risk assessment. We do this by describing the benefit flows from the natural capital assets of the region, appraising how activities are creating pressures on these flows and whether the controls for these pressures protect them. Our risk register highlights how governance currently favours the protection of direct (extractive) benefit flows from natural capital assets of the region, which are primarily targeted for financial benefit. Without a systems-based framework that can account for the cumulative pressures on natural capital assets their status, associated ecosystem services and benefits are at risk. Such an approach is essential to capture and protect the foundational and often diffuse connections between marine natural capital and global society.

Filling the data gaps: Transferring models from data-rich to data-poor deep-sea areas to support spatial management - Amelia E.H. Bridges; David K.A. Barnes; James B. Bell; Rebecca E. Ross; Lizette Voges; Kerry L. Howell (Journal of Environmental Management, 2023)

DESIGNER fraction concept unmasks minor bioactive constituents in red clover (Trifolium pratense L.) - Ryan Hitzman; Gonzalo R. Malca-Garcia; Caitlin Howell; Hyun-Young Park; J. Brent Friesen; Huali Dong; Tareisha Dunlap; James B. McAlpine; Guenter Vollmer; Maarten C. Bosland; Dejan Nikolić; David C. Lankin; et al. (Phytochemistry, 2023)

The Link Between Personality, Subjective Well-being, and Welfare in Zoo-Housed Sulawesi Crested Macaques (Macaca nigra) - Nia Parry-Howells; Kathy Baker; Holly L. Farmer (International Journal of Primatology, 2023)

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

Broad-scale benthic habitat classification of the South Atlantic - Kirsty A. McQuaid; Amelia E.H. Bridges; Kerry L. Howell; Tiago B.R. Gandra; Vitor de Souza; Jock C. Currie; Oliver T. Hogg; Tabitha R.R. Pearman; James B. Bell; Lara J. Atkinson; Diane Baum; Jarbas Bonetti; et al. (Progress in Oceanography, 2023)

A standardised ecosystem services framework for the deep sea - Giulia La Bianca; Sian Rees; Martin J. Attrill; Amanda T. Lombard; Kirsty A. McQuaid; Holly J. Niner; Henk van Rein; Kerry J. Sink; Kerry L. Howell (Frontiers in Marine Science, 2023)
Despite its remoteness, human activity has impacted the deep sea and changes to the structure and function of deep-sea ecosystems are already noticeable. In terrestrial and shallow water marine environments, demonstrating how ecosystems support human well-being has been instrumental in setting policy and management objectives for sustainable resource use. Foundational to this approach is a framework of ecosystem service (ES) classification and a synthesis of the knowledge base, which can then be used to structure decision-support tools such as ecosystem accounts or Environmental Impact Assessments. At present, no such framework exists for the deep sea. There is thus an urgent need to determine and assess the ES provided by deep-sea habitats and species before (potentially irreversible) decisions are made about deep-sea habitat use and governance. As a first step towards the incorporation of ES in such decision-making, we undertake two systematic reviews of the scientific literature based on the principles of the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) systematic process. This was to define a comparative ES framework and synthesise the current evidence base for how deep-sea habitats support ecosystem services. Our framework proposes four supporting services, three regulating services, four provisioning services and three cultural services for which there is an established and growing body of evidence for the role of deep-sea habitats. The ES framework presented here provides a structure for deep-sea ecosystem services. In its next phase of development, this could provide the foundation for the development of habitat-ecosystem service matrices, which are a critical component for truly accounting for ES in decision-making, particularly spatial management. This framework has significant implications for deep-sea management, conservation and policy, as it provides an ecosystem services-based tool that can be used in any deep-sea ecosystems management across the planet, and it also shows how critical these data gaps are for today’s decisions and how seriously they should be considered in decision-making processes.

Integrated ecosystem assessment around islands of the tropical South Mid-Atlantic Ridge - Amanda R. Rodrigues; Sergio R. Floeter; Vicente Gomes; Débora S. Ferrari; Vinicius J. Giglio; Fernanda C. Silva; Ana M. R. Liedke; Carlos E. L. Ferreira; Kerry Howell; Maria A. Gasalla (Frontiers in Marine Science, 2023)
The South Mid Atlantic Ridge comprises three main oceanic islands in the equatorial and tropical portions of the Atlantic Ocean. These islands are isolated from each other and equidistant from both the continental margins of South America and Africa, sharing common patterns but with different types of human use and pressures. Moreover, the areas beyond national jurisdiction between those islands are visited and exploited by distant fishing fleets and include large areas of shipping activity for commodities. Here, a pioneering integrated ecosystem assessment (IEA) process is constructed for the region among Saint Peter and Saint Paul’s Archipelago (Brazil), Saint Helena Island and Ascension Island (UK overseas territories). For that, we used a qualitative assessment of risks arising from anthropogenic activities, representing a novel contribution to the field. The Options for Delivering Ecosystem-Based Marine Management (ODEMM) approach was applied to trace sector–pressure–component pathways. A ‘linkage framework’ was outlined including pressures affecting each ecosystem component, and supported a process of knowledge attributions that scored the impact risks. All results were validated with regional stakeholders through workshops, including local and international management bodies, non-governmental organizations (NGOs) and scientists. The approach focused on a significant area among encompassing the open ocean, shallow and deep-sea biomes, analyzing the main sectors and pressures affecting the ecological components. Our results identified 14 sectors and 16 key pressures associated with 23 ecosystem components, totaling 780 impact chains. Fishing, shipping, wastewater, and tourism/recreation appeared as the top impacting sectors. Fishing and shipping were the most connected with ecosystem components links. Litter, species extraction, contaminants, and bycatch were the pressures that had the highest risk of impact values. Lastly, demersal and pelagic fish and pelagic and demersal elasmobranchs were the groups with the highest risk related to overall impacts, which were supported by local and regional evidence from long term monitoring programs and local studies. Our study demonstrated that these seemingly pristine islands and oceanic waters are already experiencing human impacts that should be addressed by local both conservation measures and international agreements. We also highlight the pressures that should be prioritized for better monitoring and policy, as well as those linkage components that have been less investigated.

Oceanographic variability drives the distribution but not the density of the aggregation forming deep-sea sponge Pheronema carpenteri - Kyran P. Graves; Amelia E.H. Bridges; Tomasz Dabrowski; Thomas Furey; Kieran Lyons; Kerry L. Howell (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Depth and latitudinal gradients of diversity in seamount benthic communities - Amelia E. H. Bridges; David K. A. Barnes; James B. Bell; Rebecca E. Ross; Kerry L. Howell (Journal of Biogeography, 2022)
Aim Latitudinal and bathymetric species diversity gradients in the deep sea have been identified, but studies have rarely considered these gradients across hard substratum habitats, such as seamount and oceanic island margins. This study aimed to identify whether the current understanding of latitudinal and bathymetric gradients in α‐diversity (species richness) apply to seamount ecosystems, as well as ascertaining whether identifiable trends were present in seamount β‐diversity along a bathymetric gradient. Location Exclusive Economic Zones of Saint Helena, Ascension Island and Tristan da Cunha, spanning 8–40°S in the South Atlantic. Taxon Seamount megabenthic communities. Methods Images from 39 transects, collected between 250 and 950 m, were used to characterise species richness. We subsequently applied general linear models to test possible environmental drivers across latitudinal and bathymetric ranges. Regression models were employed to investigate the β‐diversity gradient of species turnover with depth. Results Transects in temperate latitude had significantly higher species richness than those in the tropics. Surface primary productivity and substrate hardness both had significant positive effects on species richness, and a weak relationship between temperature and species richness was observed. No significant relationship between species richness and depth was detected, but there was significant species turnover with depth. Main conclusions Seamounts and oceanic islands do not conform to established depth–diversity relationships within the depth range studied. However, seamounts and oceanic islands in the South Atlantic do appear to follow a parabolic latitudinal diversity gradient, closely associated with higher productivity in temperate regions.

Extended gene panel testing in lobular breast cancer - Elke M. van Veen; D. Gareth Evans; Elaine F. Harkness; Helen J. Byers; Jamie M. Ellingford; Emma R. Woodward; Naomi L. Bowers; Andrew J. Wallace; Sacha J. Howell; Anthony Howell; Fiona Lalloo; William G. Newman; et al. (Familial Cancer, 2022)
Purpose : Lobular breast cancer (LBC) accounts for ~ 15% of breast cancer. Here, we studied the frequency of pathogenic germline variants (PGVs) in an extended panel of genes in women affected with LBC. Methods : 302 women with LBC and 1567 without breast cancer were tested for BRCA1/2 PGVs. A subset of 134 LBC affected women who tested negative for BRCA1/2 PGVs underwent extended screening, including: ATM, CDH1, CHEK2, NBN, PALB2, PTEN, RAD50, RAD51D, and TP53. Results : 35 PGVs were identified in the group with LBC, of which 22 were in BRCA1/2 . Ten actionable PGVs were identified in additional genes ( ATM (4), CDH1 (1), CHEK2 (1), PALB2 (2) and TP53 (2)). Overall, PGVs in three genes conferred a significant increased risk for LBC. Odds ratios (ORs) were: BRCA1 : OR = 13.17 (95%CI 2.83–66.38; P = 0.0017), BRCA2 : OR = 10.33 (95%CI 4.58–23.95; P < 0.0001); and ATM: OR = 8.01 (95%CI 2.52–29.92; P = 0.0053). We did not detect an increased risk of LBC for PALB2, CDH1 or CHEK2 . Conclusion : The overall PGV detection rate was 11.59%, with similar rates of BRCA1/2 (7.28%) PGVs as for other actionable PGVs (7.46%), indicating a benefit for extended panel genetic testing in LBC. We also report a previously unrecognised association of pathogenic variants in ATM with LBC.

Editorial: Biodiversity, Connectivity and Ecosystem Function Across the Clarion-Clipperton Zone: A Regional Synthesis for an Area Targeted for Nodule Mining - Craig R. Smith; Malcolm R. Clark; Erica Goetze; Adrian G. Glover; Kerry L. Howell (Frontiers in Marine Science, 2021)

Systems analysis of miRNA biomarkers to inform drug safety - Amy L. Schofield; Joseph P. Brown; Jack Brown; Ania Wilczynska; Catherine Bell; Warren E. Glaab; Matthias Hackl; Lawrence Howell; Stephen Lee; James W. Dear; Mika Remes; Paul Reeves; et al. (Archives of Toxicology, 2021)
microRNAs (miRNAs or miRs) are short non-coding RNA molecules which have been shown to be dysregulated and released into the extracellular milieu as a result of many drug and non-drug-induced pathologies in different organ systems. Consequently, circulating miRs have been proposed as useful biomarkers of many disease states, including drug-induced tissue injury. miRs have shown potential to support or even replace the existing traditional biomarkers of drug-induced toxicity in terms of sensitivity and specificity, and there is some evidence for their improved diagnostic and prognostic value. However, several pre-analytical and analytical challenges, mainly associated with assay standardization, require solutions before circulating miRs can be successfully translated into the clinic. This review will consider the value and potential for the use of circulating miRs in drug-safety assessment and describe a systems approach to the analysis of the miRNAome in the discovery setting, as well as highlighting standardization issues that at this stage prevent their clinical use as biomarkers. Highlighting these challenges will hopefully drive future research into finding appropriate solutions, and eventually circulating miRs may be translated to the clinic where their undoubted biomarker potential can be used to benefit patients in rapid, easy to use, point-of-care test systems.

Benthic Assemblage Composition of South Atlantic Seamounts - Amelia E. H. Bridges; David K. A. Barnes; James B. Bell; Rebecca E. Ross; Kerry L. Howell (Frontiers in Marine Science, 2021)
Seamounts and oceanic islands rise from the seafloor and provide suitable habitat for a diverse range of biological assemblages including Vulnerable Marine Ecosystems (VMEs). Whilst they have been the focus of some work globally, there has been little description of the biological and physical environments of seamounts in the South Atlantic Ocean. In this study, we characterized benthic assemblage composition from 13 seamounts and oceanic islands spanning 8–40°S within the exclusive economic zones (EEZs) of Ascension Island, Saint Helena and Tristan da Cunha. Drop camera imagery was collected between 170 and 1000 m. All fauna present in images were identified and quantified, and multivariate statistics were used to describe biological assemblages and identify their environmental drivers. Benthic communities of temperate regions (Tristan da Cunha archipelago) were shown to be distinct from those found in the tropics, with latitude and depth identified as key environmental drivers of assemblage composition. Our results are consistent with the current understanding of the biogeography of the South Atlantic, both in terms of the distinction between tropical and temperate regions, and the influence of depth and water mass structure on assemblage distribution. Faunal assemblages are similar to those observed in the North Atlantic in terms of functional groups. VMEs are present within the EEZs of all three territories and are potentially protected from some threats by large marine protected areas (MPAs). Our imagery, data and analyses provide a baseline for south Atlantic seamounts so that future monitoring can establish whether existing protected status is sufficient to conserve both unique biodiversity and considerable potential for vital ecosystem services.

A dry future for the Everglades favors invasive herpetofauna - Hunter J. Howell; Giacomo L. Delgado; Alyssa C. Wood; Leila M. Thompson; Eric A. Cline; Christopher A. Searcy (Biological Invasions, 2021)

Improving RNA interference in the southern green stink bug, Nezara viridula - Dhandapani Gurusamy; Jeffrey L. Howell; Shankar C. R. R. Chereddy; Kanakachari Mogilicherla; Subba Reddy Palli (Journal of Pest Science, 2021)

Using Habitat Classification to Assess Representativity of a Protected Area Network in a Large, Data-Poor Area Targeted for Deep-Sea Mining - Kirsty A. McQuaid; Martin J. Attrill; Malcolm R. Clark; Amber Cobley; Adrian G. Glover; Craig R. Smith; Kerry L. Howell (Frontiers in Marine Science, 2020)
Extractive activities in the ocean are expanding into the vast, poorly studied deep sea, with the consequence that environmental management decisions must be made for data-poor seafloor regions. Habitat classification can support marine spatial planning and inform decision-making processes in such areas. We present a regional, top–down, broad-scale, seafloor-habitat classification for the Clarion-Clipperton Fracture Zone (CCZ), an area targeted for future polymetallic nodule mining in abyssal waters in the equatorial Pacific Ocean. Our classification uses non-hierarchical, k-medoids clustering to combine environmental correlates of faunal distributions in the region. The classification uses topographic variables, particulate organic carbon flux to the seafloor, and is the first to use nodule abundance as a habitat variable. Twenty-four habitat classes are identified, with large expanses of abyssal plain and smaller classes with varying topography, food supply, and substrata. We then assess habitat representativity of the current network of protected areas (called Areas of Particular Environmental Interest) in the CCZ. Several habitat classes with high nodule abundance are common in mining exploration claims, but currently receive little to no protection in APEIs. There are several large unmanaged areas containing high nodule abundance on the periphery of the CCZ, as well as smaller unmanaged areas within the central CCZ, that could be considered for protection from mining to improve habitat representativity and safeguard regional biodiversity.

Effects of early life stress on cocaine intake in male and female rhesus macaques - Alison G. P. Wakeford; Brik Kochoian; Erin R. Siebert; Sarah Katznelson; Elyse L. Morin; Brittany R. Howell; Kai M. McCormack; Michael A. Nader; Mar M. Sanchez; Leonard L. Howell (Psychopharmacology, 2020)

A Blueprint for an Inclusive, Global Deep-Sea Ocean Decade Field Program - Kerry L. Howell; Ana Hilário; A. Louise Allcock; David M. Bailey; Maria Baker; Malcolm R. Clark; Ana Colaço; Jon Copley; Erik E. Cordes; Roberto Danovaro; Awantha Dissanayake; Elva Escobar; et al. (Frontiers in Marine Science, 2020)
The ocean plays a crucial role in the functioning of the Earth System and in the provision of vital goods and services. The United Nations (UN) declared 2021–2030 as the UN Decade of Ocean Science for Sustainable Development. The Roadmap for the Ocean Decade aims to achieve six critical societal outcomes (SOs) by 2030, through the pursuit of four objectives (Os). It specifically recognizes the scarcity of biological data for deep-sea biomes, and challenges the global scientific community to conduct research to advance understanding of deep-sea ecosystems to inform sustainable management. In this paper, we map four key scientific questions identified by the academic community to the Ocean Decade SOs: (i) What is the diversity of life in the deep ocean? (ii) How are populations and habitats connected? (iii) What is the role of living organisms in ecosystem function and service provision? and (iv) How do species, communities, and ecosystems respond to disturbance? We then consider the design of a global-scale program to address these questions by reviewing key drivers of ecological pattern and process. We recommend using the following criteria to stratify a global survey design: biogeographic region, depth, horizontal distance, substrate type, high and low climate hazard, fished/unfished, near/far from sources of pollution, licensed/protected from industry activities. We consider both spatial and temporal surveys, and emphasize new biological data collection that prioritizes southern and polar latitudes, deeper (> 2000 m) depths, and midwater environments. We provide guidance on observational, experimental, and monitoring needs for different benthic and pelagic ecosystems. We then review recent efforts to standardize biological data and specimen collection and archiving, making “sampling design to knowledge application” recommendations in the context of a new global program. We also review and comment on needs, and recommend actions, to develop capacity in deep-sea research; and the role of inclusivity - from accessing indigenous and local knowledge to the sharing of technologies - as part of such a global program. We discuss the concept of a new global deep-sea biological research program ‘ Challenger 150 ,’ highlighting what it could deliver for the Ocean Decade and UN Sustainable Development Goal 14.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Transcriptomic analysis of hidradenitis suppurativa skin suggests roles for multiple inflammatory pathways in disease pathogenesis - Beth E. Rumberger; Erika L. Boarder; Sherry L. Owens; Michael D. Howell (Inflammation Research, 2020)

Comparing Deep-Sea Larval Dispersal Models: A Cautionary Tale for Ecology and Conservation - Rebecca E. Ross; W. Alex M. Nimmo-Smith; Ricardo Torres; Kerry L. Howell (Frontiers in Marine Science, 2020)

Use of standardized methods to improve extinction‐risk classification - Caitlin C. Mothes; Stephanie L. Clements; Dishane K. Hewavithana; Hunter J. Howell; Aaron S. David; Nicole D. Leventhal; Christopher A. Searcy (Conservation Biology, 2020)
Standardized classification methods based on quantifiable risk metrics are critical for evaluating extinction threats because they increase objectivity, consistency, and transparency of listing decisions. Yet, in the United States, neither federal nor state agencies use standardized methods for listing species for legal protection, which could put listing decisions at odds with the magnitude of the risk. We used a recently developed set of quantitative risk metrics for California herpetofauna as a case study to highlight discrepancies in listing decisions made without standardized methods. We also combined such quantitative metrics with classification tree analysis to attempt to increase the transparency of previous listing decisions by identifying the criteria that had inherently been given the most weight. Federally listed herpetofauna in California scored significantly higher on the risk‐metric spectrum than those not federally listed, whereas state‐listed species did not score any higher than species that were not state listed. Based on classification trees, state endemism was the most important predictor of listing status at the state level and distribution trend (decline in a species’ range size) and population trend (decline in a species’ abundance at localized sites) were the most important predictors at the federal level. Our results emphasize the need for governing bodies to adopt standardized methods for assessing conservation risk that are based on quantitative criteria. Such methods allow decision makers to identify criteria inherently given the most weight in determining listing status, thus increasing the transparency of previous listing decisions, and produce an unbiased comparison of conservation threat across all species to promote consistency, efficiency, and effectiveness of the listing process.

Comparison of the Hepatotoxic Potential of Two Treatments for Autosomal-Dominant Polycystic Kidney DiseaseUsing Quantitative Systems Toxicology Modeling - J. L. Woodhead; L. Pellegrini; L. K. M. Shoda; B. A. Howell (Pharmaceutical Research, 2020)
Purpose Autosomal-dominant polycystic kidney disease (ADPKD) is an orphan disease with few current treatment options. The vasopressin V 2 receptor antagonist tolvaptan is approved in multiple countries for the treatment of ADPKD, however its use is associated with clinically significant drug-induced liver injury. Methods In prior studies, the potential for hepatotoxicity of tolvaptan was correctly predicted using DILIsym®, a quantitative systems toxicology (QST) mathematical model of drug-induced liver injury. In the current study, we evaluated lixivaptan, another proposed ADPKD treatment and vasopressin V 2 receptor antagonist, using DILIsym®. Simulations were conducted that assessed the potential for lixivaptan and its three main metabolites to cause hepatotoxicity due to three injury mechanisms: bile acid accumulation, mitochondrial dysfunction, and oxidative stress generation. Results of these simulations were compared to previously published DILIsym results for tolvaptan. Results No ALT elevations were predicted to occur at the proposed clinical dose for lixivaptan, in contrast to previously published simulation results for tolvaptan. As such, lixivaptan was predicted to have a markedly lower risk of hepatotoxicity compared to tolvaptan with respect to the hepatotoxicity mechanisms represented in DILIsym. Conclusions These results demonstrate the potential for using QST methods to differentiate drugs in the same class for their potential to cause hepatotoxicity.

Correction to: Effects of New Zealand blackcurrant extract on sport climbing performance - J. A. Potter; C. I. Hodgson; M. Broadhurst; L. Howell; J. Gilbert; M. E. T. Willems; I. C. Perkins (European Journal of Applied Physiology, 2020)

Effects of New Zealand blackcurrant extract on sport climbing performance - J. A. Potter; C. I. Hodgson; M. Broadhurst; L. Howell; J. Gilbert; M. E. T. Willems; I. C. Perkins (European Journal of Applied Physiology, 2020)

Combining Distribution and Dispersal Models to Identify a Particularly Vulnerable Marine Ecosystem - Rebecca E. Ross; Edward J. G. Wort; Kerry L. Howell (Frontiers in Marine Science, 2019)

Effects of early life stress on cocaine self-administration in post-pubertal male and female rhesus macaques - Alison G. P. Wakeford; Elyse L. Morin; Sara N. Bramlett; Brittany R. Howell; Kai M. McCormack; Jerrold S. Meyer; Michael A. Nader; Mar M. Sanchez; Leonard L. Howell (Psychopharmacology, 2019)

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

Effects of ketamine treatment on cocaine-induced reinstatement and disruption of functional connectivity in unanesthetized rhesus monkeys - Eric A. Maltbie; Kaundinya S. Gopinath; Leonard L. Howell (Psychopharmacology, 2019)

Analyzing the Mechanisms Behind Macrolide Antibiotic-Induced Liver Injury Using Quantitative Systems Toxicology Modeling - Jeffrey L. Woodhead; Kyunghee Yang; David Oldach; Chris MacLauchlin; Prabhavathi Fernandes; Paul B. Watkins; Scott Q. Siler; Brett A. Howell (Pharmaceutical Research, 2019)

Episodic diamond growth beneath the Kaapvaal Craton at Jwaneng Mine, Botswana - Michael U. Gress; Daniel Howell; Ingrid L. Chinn; Laura Speich; Simon C. Kohn; Quint van den Heuvel; Ellen Schulten; Anna S. M. Pals; Gareth R. Davies (Mineralogy and Petrology, 2018)

Genomic and transcriptomic signals of thermal tolerance in heat‐tolerant corals ( Platygyra daedalea ) of the Arabian/Persian Gulf - Nathan L. Kirk; Emily J. Howells; David Abrego; John A. Burt; Eli Meyer (Molecular Ecology, 2018)
Scleractinian corals occur in tropical regions near their upper thermal limits and are severely threatened by rising ocean temperatures. However, several recent studies have shown coral populations can harbour genetic variation in thermal tolerance. Here, we have extended these approaches to study heat tolerance of corals in the Persian/Arabian Gulf, where heat‐tolerant local populations experience extreme summer temperatures (up to 36°C). To evaluate whether selection has depleted genetic variation in thermal tolerance, estimate potential future adaptive responses and understand the functional basis for these corals’ unusual heat tolerance, we conducted controlled crosses in the Gulf coral Platygyra daedalea . Heat tolerance is highly heritable in this population ( h 2 = 0.487–0.748), suggesting substantial potential for adaptive responses to selection for elevated temperatures. To identify genetic markers associated with this variation, we conducted genomewide SNP genotyping in parental corals and tested for relationships between paternal genotype and offspring thermal tolerance. Resulting multilocus SNP genotypes explained a large fraction of variation in thermal tolerance in these crosses (69%). To investigate the functional basis of these differences in thermal tolerance, we profiled transcriptional responses in tolerant and susceptible families, revealing substantial sire effects on transcriptional responses to thermal stress. We also studied sequence variation in these expressed sequences, identifying alleles and functional groups of differentially expressed genes associated with thermal tolerance. Our findings demonstrate that corals in this population harbour extensive genetic variation in thermal tolerance, and heat‐tolerant phenotypes differ in both gene sequences and transcriptional stress responses from their susceptible counterparts.

Modelling tidally induced larval dispersal over Anton Dohrn Seamount - Nataliya Stashchuk; Vasiliy Vlasenko; Kerry L. Howell (Ocean Dynamics, 2018)

(±)-MDMA and its enantiomers: potential therapeutic advantages of R(−)-MDMA - Elizabeth G. Pitts; Daniel W. Curry; Karly N. Hampshire; Matthew B. Young; Leonard L. Howell (Psychopharmacology, 2018)

Projecting Marine Mammal Distribution in a Changing Climate - Gregory K. Silber; Matthew D. Lettrich; Peter O. Thomas; Jason D. Baker; Mark Baumgartner; Elizabeth A. Becker; Peter Boveng; Dorothy M. Dick; Jerome Fiechter; Jaume Forcada; Karin A. Forney; Roger B. Griffis; et al. (Frontiers in Marine Science, 2017)

Inhibition of serotonin transporters disrupts the enhancement of fear memory extinction by 3,4-methylenedioxymethamphetamine (MDMA) - Matthew B. Young; Seth D. Norrholm; Lara M. Khoury; Tanja Jovanovic; Sheila A.M. Rauch; Collin M. Reiff; Boadie W. Dunlop; Barbara O. Rothbaum; Leonard L. Howell (Psychopharmacology, 2017)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Effects of the serotonin 2C receptor agonist WAY163909 on the abuse-related effects and mesolimbic dopamine neurochemistry induced by abused stimulants in rhesus monkeys - Laís F. Berro; Maylen Perez Diaz; Eric Maltbie; Leonard L. Howell (Psychopharmacology, 2017)

Assessment of tolerance to the effects of methamphetamine on daytime and nighttime activity evaluated with actigraphy in rhesus monkeys - Laís F. Berro; Monica L. Andersen; Leonard L. Howell (Psychopharmacology, 2017)

Complexity and health functionality of plant cell wall fibers from fruits and vegetables - A. Padayachee; L. Day; K. Howell; M. J. Gidley (Critical Reviews in Food Science and Nutrition, 2017)

Raman spectroscopic analysis of the effect of the lichenicolous fungus Xanthoriicola physciae on its lichen host - Howell G.M. Edwards; Mark R.D. Seaward; Tom F. Preece; Susana E. Jorge-Villar; David L. Hawksworth (Symbiosis, 2017)

Anemonefish musical chairs and the plight of the two-band anemonefish, Amphiprion bicinctus - Jacob Howell; Tamar L. Goulet; Denis Goulet (Environmental Biology of Fishes, 2016)

Reduced glutamate in white matter of male neonates exposed to alcohol in utero: a 1H-magnetic resonance spectroscopy study - F. M. Howells; K. A. Donald; A. Roos; R. P. Woods; H. J. Zar; K. L. Narr; D. J. Stein (Metabolic Brain Disease, 2016)

Land cover change and carbon emissions over 100 years in an A frican biodiversity hotspot - Simon Willcock; Oliver L. Phillips; Philip J. Platts; Ruth D. Swetnam; Andrew Balmford; Neil D. Burgess; Antje Ahrends; Julian Bayliss; Nike Doggart; Kathryn Doody; Eibleis Fanning; Jonathan M. H. Green; et al. (Global Change Biology, 2016)
Agricultural expansion has resulted in both land use and land cover change ( LULCC ) across the tropics. However, the spatial and temporal patterns of such change and their resulting impacts are poorly understood, particularly for the presatellite era. Here, we quantify the LULCC history across the 33.9 million ha watershed of Tanzania's Eastern Arc Mountains, using geo‐referenced and digitized historical land cover maps (dated 1908, 1923, 1949 and 2000). Our time series from this biodiversity hotspot shows that forest and savanna area both declined, by 74% (2.8 million ha) and 10% (2.9 million ha), respectively, between 1908 and 2000. This vegetation was replaced by a fivefold increase in cropland, from 1.2 million ha to 6.7 million ha. This LULCC implies a committed release of 0.9 Pg C (95% CI : 0.4–1.5) across the watershed for the same period, equivalent to 0.3 Mg C ha −1 yr −1 . This is at least threefold higher than previous estimates from global models for the same study area. We then used the LULCC data from before and after protected area creation, as well as from areas where no protection was established, to analyse the effectiveness of legal protection on land cover change despite the underlying spatial variation in protected areas. We found that, between 1949 and 2000, forest expanded within legally protected areas, resulting in carbon uptake of 4.8 (3.8–5.7) Mg C ha −1 , compared to a committed loss of 11.9 (7.2–16.6) Mg C ha −1 within areas lacking such protection. Furthermore, for nine protected areas where LULCC data are available prior to and following establishment, we show that protection reduces deforestation rates by 150% relative to unprotected portions of the watershed. Our results highlight that considerable LULCC occurred prior to the satellite era, thus other data sources are required to better understand long‐term land cover trends in the tropics.

Host adaptation and unexpected symbiont partners enable reef‐building corals to tolerate extreme temperatures - Emily J. Howells; David Abrego; Eli Meyer; Nathan L. Kirk; John A. Burt (Global Change Biology, 2016)
Understanding the potential for coral adaptation to warming seas is complicated by interactions between symbiotic partners that define stress responses and the difficulties of tracking selection in natural populations. To overcome these challenges, we characterized the contribution of both animal host and symbiotic algae to thermal tolerance in corals that have already experienced considerable warming on par with end‐of‐century projections for most coral reefs. Thermal responses in Platygyra daedalea corals from the hot Persian Gulf where summer temperatures reach 36°C were compared with conspecifics from the milder Sea of Oman. Persian Gulf corals had higher rates of survival at elevated temperatures (33 and 36°C) in both the nonsymbiotic larval stage (32–49% higher) and the symbiotic adult life stage (51% higher). Additionally, Persian Gulf hosts had fixed greater potential to mitigate oxidative stress (31–49% higher) and their Symbiodinium partners had better retention of photosynthetic performance under elevated temperature (up to 161% higher). Superior thermal tolerance of Persian Gulf vs. Sea of Oman corals was maintained after 6‐month acclimatization to a common ambient environment and was underpinned by genetic divergence in both the coral host and symbiotic algae. In P. daedalea host samples, genomewide SNP variation clustered into two discrete groups corresponding with Persian Gulf and Sea of Oman sites. Symbiodinium within host tissues predominantly belonged to ITS 2 rDNA type C3 in the Persian Gulf and type D1a in the Sea of Oman contradicting patterns of Symbiodinium thermal tolerance from other regions. Our findings provide evidence that genetic adaptation of both host and Symbiodinium has enabled corals to cope with extreme temperatures in the Persian Gulf. Thus, the persistence of coral populations under continued warming will likely be determined by evolutionary rates in both, rather than single, symbiotic partners.

Microsatellite allele sizes alone are insufficient to delineate species boundaries in Symbiodinium - E. J. Howells; B. L. Willis; L. K. Bay; M. J. H. van Oppen (Molecular Ecology, 2016)
Symbiodinium are a diverse group of unicellular dinoflagellates that are important nutritional symbionts of reef‐building corals. Symbiodinium putative species (‘types’) are commonly identified with genetic markers, mostly nuclear and chloroplast encoded ribosomal DNA regions. Population genetic analyses using microsatellite loci have provided insights into Symbiodinium biogeography, connectivity and phenotypic plasticity, but are complicated by: (i) a lack of consensus criteria used to delineate inter‐ vs. intragenomic variation within species; and (ii) the high density of Symbiodinium in host tissues, which results in single samples comprising thousands of individuals. To address this problem, Wham & LaJeunesse (2016) present a method for identifying cryptic Symbiodinium species from microsatellite data based on correlations between allele size distributions and nongeographic genetic structure. Multilocus genotypes that potentially do not recombine in sympatry are interpreted as secondary ‘species’ to be discarded from downstream population genetic analyses. However, Symbiodinium species delineations should ideally incorporate multiple physiological, ecological and molecular criteria. This is because recombination tests may be a poor indicator of species boundaries in Symbiodinium due to their predominantly asexual mode of reproduction. Furthermore, discontinuous microsatellite allele sizes in sympatry may be explained by secondary contact between previously isolated populations and by mutations that occur in a nonstepwise manner. Limitations of using microsatellites alone to delineate species are highlighted in earlier studies that demonstrate occasional bimodal distributions of allele sizes within Symbiodinium species and considerable allele size sharing among Symbiodinium species. We outline these issues and discuss the validity of reinterpretations of our previously published microsatellite data from Symbiodinium populations on the Great Barrier Reef (Howells et al . 2013).

PCDD/F and PCB water column partitioning examination using natural organic matter and black carbon partition coefficient models - Nathan L. Howell; Hanadi S. Rifai (Environmental Science and Pollution Research, 2016)

Alcohol exposure in utero is associated with decreased gray matter volume in neonates - Kirsten A. Donald; J. P. Fouche; Annerine Roos; Nastassja Koen; Fleur M. Howells; Edward P. Riley; Roger P. Woods; Heather J. Zar; Katherine L. Narr; Dan J. Stein (Metabolic Brain Disease, 2016)

Biogenesis of P seudomonas aeruginosa type IV pili and regulation of their function - Tiffany L. Leighton; Ryan N. C. Buensuceso; P. Lynne Howell; Lori L. Burrows (Environmental Microbiology, 2015)
Summary Type IV pili ( T4P ) are bacterial virulence factors involved in a wide variety of functions including deoxyribonucleic acid uptake, surface attachment, biofilm formation and twitching motility. While T4P are common surface appendages, the systems that assemble them and the regulation of their function differ between species. Pseudomonas aeruginosa , N eisseria spp. and M yxococcus xanthus are common model systems used to study T4P biology. This review focuses on recent advances in P . aeruginosa T4P structural biology, and the regulatory pathways controlling T4P biogenesis and function.

MITOsym®: A Mechanistic, Mathematical Model of Hepatocellular Respiration and Bioenergetics - Y. Yang; S. Nadanaciva; Y. Will; J. L. Woodhead; B. A. Howell; P. B. Watkins; S. Q. Siler (Pharmaceutical Research, 2015)

Habitat fragmentation in coastal southern C alifornia disrupts genetic connectivity in the cactus wren ( C ampylorhynchus brunneicapillus ) - Kelly R. Barr; Barbara E. Kus; Kristine L. Preston; Scarlett Howell; Emily Perkins; Amy G. Vandergast (Molecular Ecology, 2015)
Achieving long‐term persistence of species in urbanized landscapes requires characterizing population genetic structure to understand and manage the effects of anthropogenic disturbance on connectivity. Urbanization over the past century in coastal southern C alifornia has caused both precipitous loss of coastal sage scrub habitat and declines in populations of the cactus wren ( C ampylorhynchus brunneicapillus ). Using 22 microsatellite loci, we found that remnant cactus wren aggregations in coastal southern C alifornia comprised 20 populations based on strict exact tests for population differentiation, and 12 genetic clusters with hierarchical B ayesian clustering analyses. Genetic structure patterns largely mirrored underlying habitat availability, with cluster and population boundaries coinciding with fragmentation caused primarily by urbanization. Using a habitat model we developed, we detected stronger associations between habitat‐based distances and genetic distances than E uclidean geographic distance. Within populations, we detected a positive association between available local habitat and allelic richness and a negative association with relatedness. Isolation‐by‐distance patterns varied over the study area, which we attribute to temporal differences in anthropogenic landscape development. We also found that genetic bottleneck signals were associated with wildfire frequency. These results indicate that habitat fragmentation and alterations have reduced genetic connectivity and diversity of cactus wren populations in coastal southern C alifornia. Management efforts focused on improving connectivity among remaining populations may help to ensure population persistence.

Estimating dispersal distance in the deep sea: challenges and applications to marine reserves - Ana HilÃ¡rio; Anna Metaxas; Sylvie M. Gaudron; Kerry L. Howell; Annie Mercier; NÃ©lia C. Mestre; Rebecca E. Ross; Andreas M. Thurnherr; Craig Young (Frontiers in Marine Science, 2015)

Functional connectivity in frontal-striatal brain networks and cocaine self-administration in female rhesus monkeys - K. S. Murnane; K. S. Gopinath; E. Maltbie; J. B. Daunais; Q. K. Telesford; L. L. Howell (Psychopharmacology, 2015)

Mindfulness based cognitive therapy may improve emotional processing in bipolar disorder: pilot ERP and HRV study - Fleur M. Howells; H. G. Laurie Rauch; Victoria L. Ives-Deliperi; Neil R. Horn; Dan J. Stein (Metabolic Brain Disease, 2014)

Breast cancer risk assessment in 8,824 women attending a family history evaluation and screening programme - D. Gareth R. Evans; Sarah Ingham; Sarah Dawe; L. Roberts; F. Lalloo; A. R. Brentnall; P. Stavrinos; Anthony Howell (Familial Cancer, 2014)

Changing sea ice conditions and marine transportation activity in Canadian Arctic waters between 1990 and 2012 - Larissa Pizzolato; Stephen E. L. Howell; Chris Derksen; Jackie Dawson; Luke Copland (Climatic Change, 2014)

Mammographic surveillance in women aged 35–39 at enhanced familial risk of breast cancer (FH02) - D. G. Evans; S. Thomas; J. Caunt; L. Roberts; A. Howell; M. Wilson; R. Fox; D. M. Sibbering; S. Moss; M. G. Wallis; D. M. Eccles; S. Duffy (Familial Cancer, 2014)

Transgene delivery via intracellular electroporetic nanoinjection - Aubrey M. Wilson; Quentin T. Aten; Nathan C. Toone; Justin L. Black; Brian D. Jensen; Susan Tamowski; Larry L. Howell; Sandra H. Burnett (Transgenic Research, 2013)

Spatial and temporal genetic structure of S ymbiodinium populations within a common reef‐building coral on the G reat B arrier R eef - Emily J. Howells; Bette L. Willis; Line K. Bay; Madeleine J. H. van Oppen (Molecular Ecology, 2013)
The dinoflagellate photosymbiont Symbiodinium plays a fundamental role in defining the physiological tolerances of coral holobionts, but little is known about the dynamics of these endosymbiotic populations on coral reefs. Sparse data indicate that Symbiodinium populations show limited spatial connectivity; however, no studies have investigated temporal dynamics for in hospite Symbiodinium populations following significant mortality and recruitment events in coral populations. We investigated the combined influences of spatial isolation and disturbance on the population dynamics of the generalist Symbiodinium type C2 ( ITS 1 rDNA ) hosted by the scleractinian coral Acropora millepora in the central Great Barrier Reef. Using eight microsatellite markers, we genotyped Symbiodinium in a total of 401 coral colonies, which were sampled from seven sites across a 12‐year period including during flood plume–induced coral bleaching. Genetic differentiation of Symbiodinium was greatest within sites, explaining 70–86% of the total genetic variation. An additional 9–27% of variation was explained by significant differentiation of populations among sites separated by 0.4–13 km, which is consistent with low levels of dispersal via water movement and historical disturbance regimes. Sampling year accounted for 6–7% of total genetic variation and was related to significant coral mortality following severe bleaching in 1998 and a cyclone in 2006. Only 3% of the total genetic variation was related to coral bleaching status, reflecting generally small (8%) reductions in allelic diversity within bleached corals. This reduction probably reflected a loss of genotypes in hospite during bleaching, although no site‐wide changes in genetic diversity were observed. Combined, our results indicate the importance of disturbance regimes acting together with limited oceanographic transport to determine the genetic composition of Symbiodinium types within reefs.

Novel Mutations Mapping to the Fourth Sodium Channel Domain of Nav1.7 Result in Variable Clinical Manifestations of Primary Erythromelalgia - Roman Cregg; Bisola Laguda; Robert Werdehausen; James J. Cox; John E. Linley; Juan D. Ramirez; Istvan Bodi; Michael Markiewicz; Kevin J. Howell; Ya-Chun Chen; Karen Agnew; Henry Houlden; et al. (NeuroMolecular Medicine, 2013)

Effects of methamphetamine self-administration on actigraphy-based sleep parameters in rhesus monkeys - Monica L. Andersen; Maylen P. Diaz; Kevin S. Murnane; Leonard L. Howell (Psychopharmacology, 2013)

Global population divergence of the sea star Hippasteria phrygiana corresponds to the onset of the last glacial period of the Pleistocene - D. W. Foltz; S. D. Fatland; M. Eléaume; K. Markello; K. L. Howell; K. Neill; C. L. Mah (Marine Biology, 2013)

Historical thermal regimes define limits to coral acclimatization - Emily J. Howells; Ray Berkelmans; Madeleine J. H. van Oppen; Bette L. Willis; Line K. Bay (Ecology, 2013)
Knowledge of the degree to which corals undergo physiological acclimatization or genetic adaptation in response to changes in their thermal environment is crucial to the success of coral reef conservation strategies. The potential of corals to acclimatize to temperatures exceeding historical thermal regimes was investigated by reciprocal transplantation of Acropora millepora colonies between the warm central and cool southern regions of the Great Barrier Reef (GBR) for a duration of 14 months. Colony fragments retained at native sites remained healthy, whereas transplanted fragments, although healthy over initial months when temperatures remained within native thermal regimes, subsequently bleached and suffered mortality during seasonal temperature extremes. Corals hosting Symbiodinium D transplanted to the southern GBR bleached in winter and the majority suffered whole (40%; n = 20 colonies) or partial (50%) mortality at temperatures 1.1°C below their 15‐year native minimum. In contrast, corals hosting Symbiodinium C2 transplanted to the central GBR bleached in summer and suffered whole (50%; n = 10 colonies) or partial (42%) mortality at temperatures 2.5°C above their 15‐year native maximum. During summer bleaching, the dominant Symbiodinium type changed from C2 to D within corals transplanted to the central GBR. Corals transplanted to the cooler, southern GBR grew 74–80% slower than corals at their native site, and only 50% of surviving colonies reproduced, at least partially because of cold water bleaching of transplants. Despite the absence of any visual signs of stress, corals transplanted to the warmer, central GBR grew 52–59% more slowly than corals at their native site before the summer bleaching (i.e., from autumn to spring). Allocation of energy to initial acclimatization or reproduction may explain this pattern, as the majority (65%) of transplants reproduced one month earlier than portions of the same colonies retained at the southern native site. All parameters investigated (bleaching, mortality, Symbiodinium type fidelity, reproductive timing) demonstrated strong interactions between genotype and environment, indicating that the acclimatization potential of A. millepora populations may be limited by adaptation of the holobiont to native thermal regimes.

Platelet development in cuboid diamonds: insights from micro-FTIR mapping - D. Howell; C. J. O’Neill; K. J. Grant; W. L. Griffin; S. Y. O’Reilly; N. J. Pearson; R. A. Stern; T. Stachel (Contributions to Mineralogy and Petrology, 2012)

Nanoinjection: pronuclear DNA delivery using a charged lance - Quentin T. Aten; Brian D. Jensen; Susan Tamowski; Aubrey M. Wilson; Larry L. Howell; Sandra H. Burnett (Transgenic Research, 2012)

Variability and change in the Canadian cryosphere - C. Derksen; S. L. Smith; M. Sharp; L. Brown; S. Howell; L. Copland; D. R. Mueller; Y. Gauthier; C. G. Fletcher; A. Tivy; M. Bernier; J. Bourgeois; et al. (Climatic Change, 2012)
During the International Polar Year (IPY), comprehensive observational research programs were undertaken to increase our understanding of the Canadian polar cryosphere response to a changing climate. Cryospheric components considered were snow, permafrost, sea ice, freshwater ice, glaciers and ice shelves. Enhancement of conventional observing systems and retrieval algorithms for satellite measurements facilitated development of a snapshot of current cryospheric conditions, providing a baseline against which future change can be assessed. Key findings include: 1. surface air temperatures across the Canadian Arctic exhibit a warming trend in all seasons over the past 40 years. A consistent pan-cryospheric response to these warming temperatures is evident through the analysis of multi-decadal datasets; 2. in recent years (including the IPY period) a higher rate of change was observed compared to previous decades including warming permafrost, reduction in snow cover extent and duration, reduction in summer sea ice extent, increased mass loss from glaciers, and thinning and break-up of the remaining Canadian ice shelves. These changes illustrate both a reduction in the spatial extent and mass of the cryosphere and an increase in the temporal persistence of melt related parameters. The observed changes in the cryosphere have important implications for human activity including the close ties of northerners to the land, access to northern regions for natural resource development, and the integrity of northern infrastructure.

In vitro to in vivo extrapolation and species response comparisons for drug-induced liver injury (DILI) using DILIsym™: a mechanistic, mathematical model of DILI - Brett A. Howell; Yuching Yang; Rukmini Kumar; Jeffrey L. Woodhead; Alison H. Harrill; Harvey J. Clewell; Melvin E. Andersen; Scott Q. Siler; Paul B. Watkins (Journal of Pharmacokinetics and Pharmacodynamics, 2012)

An All-Atom Model of the Structure of Human Copper Transporter 1 - Igor F. Tsigelny; Yuriy Sharikov; Jerry P. Greenberg; Mark A. Miller; Valentina L. Kouznetsova; Christopher A. Larson; Stephen B. Howell (Cell Biochemistry and Biophysics, 2012)

Estimating the carrying capacity of French Frigate Shoals for the endangered Hawaiian monk seal using Ecopath with Ecosim - Frank A. Parrish; Evan A. Howell; George A. Antonelis; Sara J. Iverson; Charles L. Littnan; James D. Parrish; Jeffrey J. Polovina (Marine Mammal Science, 2012)
The carrying capacity of the French Frigate Shoals (FFS) region for the endangered Hawaiian monk seal was appraised using an updated version of the original FFS Ecopath model ( Polovina 1984 ). Model parameters were updated using recent literature, and data from surveys of the seal population and its bottom‐associated prey. Together they produced a static mass balance model for 1998 when the prey surveys began. The Ecopath‐estimated monk seal biomass was 0.0045 t/km 2 , which was in close agreement with the biomass calculated from monk seal field beach counts (0.0046 t/km 2 ). Model simulations through time were done in Ecosim using the Ecopath balanced model and included fisheries data time series from 1998 to 2008. Monk seal biomass declined concurrently with decreases in benthic bottomfish biomass, which were influenced by large‐scale changes in the environment of the North Pacific. This model scenario was extended from 2010, when the last permitted fishery in the Northwestern Hawaiian Islands was closed, through to 2040, assuming a constant environmental signal. Model results for this time period did not show a recovery of monk seals that exceeded the initial 1998 model biomass levels, highlighting the importance of including environmental variability in estimates of monk seals recovery at FFS.

Use of Data on Avian Demographics and Site Persistence during Overwintering to Assess Quality of Restored Riparian Habitat - STEVEN C. LATTA; CHRISTINE A. HOWELL; MARK D. DETTLING; RENÉE L. CORMIER (Conservation Biology, 2012)
Monitoring responses by birds to restoration of riparian vegetation is relatively cost‐effective, but in most assessments species‐specific abundances, not demography, are monitored. Data on birds collected during the nonbreeding season are particularly lacking. We captured birds in mist nets and resighted banded birds to estimate species richness and diversity, abundance, demographic indexes, and site‐level persistence of permanent‐resident and overwintering migrants in remnant and restored riparian sites in California. Species richness in riparian remnants was significantly higher than in restored sites because abundances of uncommon permanent residents were greater in remnants. Species richness of overwintering migrants did not differ between remnants and restored sites. Responses among overwintering migrants (but not permanent residents) to remnant and restored riparian sites differed. Capture rates were higher in remnant or restored riparian sites for 7 of 10 overwintering migratory species. For Lincoln's Sparrows (Melospiza lincolnii) and White‐crowned Sparrows (Zonotrichia leucophrys) proportions of older birds were significantly higher in remnants, even though capture rates of these species were higher in restored sites. Overwinter persistence of 4 migrant species was significantly higher in remnant than in restored sites. A higher proportion of Hermit Thrushes (Catharus guttatus, 56.3%), older Fox Sparrows (Passerella iliaca, 57.1%), Lincoln's Sparrows (59.7%), and White‐crowned Sparrows (67.8%) persisted in remnants than restored sites. Our results suggest restored riparian sites provide habitat for a wide variety of species in comparable abundances and diversity as occurs in remnant riparian sites. Our demographic and persistence data showed that remnants supported some species and age classes to a greater extent than restored sites.

Erratum to: Quantifying strain birefringence halos around inclusions in diamond - D. Howell; I. G. Wood; D. P. Dobson; A. P. Jones; L. Nasdala; J. W. Harris (Contributions to Mineralogy and Petrology, 2011)

Neuroimaging and drug taking in primates - Kevin S. Murnane; Leonard L. Howell (Psychopharmacology, 2011)

Pacific Atmospheric Sulfur Experiment (PASE): dynamics and chemistry of the south Pacific tropical trade wind regime - Alan Bandy; Ian C. Faloona; Byron W. Blomquist; Barry J. Huebert; Antony D. Clarke; Steven G. Howell; R. L. Mauldin; Christopher A. Cantrell; James G. Hudson; Brian G. Heikes; John T. Merrill; Yuhang Wang; et al. (Journal of Atmospheric Chemistry, 2011)

Acute brain metabolic effects of cocaine in rhesus monkeys with a history of cocaine use - Porche’ Kirkland Henry; Kevin S. Murnane; John R. Votaw; Leonard L. Howell (Brain Imaging and Behavior, 2010)

Quantifying strain birefringence halos around inclusions in diamond - D. Howell; I. G. Wood; D. P. Dobson; A. P. Jones; L. Nasdala; J. W. Harris (Contributions to Mineralogy and Petrology, 2010)

Mounting evidence: near‐slope seamounts are faunally indistinct from an adjacent bank - Kerry L. Howell; Sophie L. Mowles; Andrew Foggo (Marine Ecology, 2010)
Seamounts have been described as island habitats harbouring a unique fauna, and as biodiversity hotspots with high rates of endemism. However, recent research suggests that these generalisations are inappropriate and poorly supported, though appropriate on and off seamount comparative data are lacking. This study uses quantitative data derived from video analysis to compare epibenthic megafaunal community composition, diversity and potential species endemism on two seamounts and one bank in the Rockall Trough region of the NE Atlantic. Sample data were standardised for substratum type across all three features and as far as possible for depth and geomorphological variation. The results suggest that under similar environmental conditions, e.g . similar substratum, depth and geomorphology, there is little difference between the communities of the bank and seamounts in the Rockall Trough. Where differences are observed, the ‘guyot’ seamount is as different to the conical seamount as it is to the bank. The seamounts are no more or less diverse than the bank; endemism is low or non‐existent. The results are discussed in the context of the common generalisations made concerning seamount communities and the implications for conservation and management of the deep sea.

Dopamine transporter-related effects of modafinil in rhesus monkeys - Monica L. Andersen; Eileen Kessler; Kevin S. Murnane; Jessica C. McClung; Sergio Tufik; Leonard L. Howell (Psychopharmacology, 2010)

Reinstatement of extinguished amphetamine self-administration by 3,4-methylenedioxymethamphetamine (MDMA) and its enantiomers in rhesus monkeys - Jessica McClung; William Fantegrossi; Leonard L. Howell (Psychopharmacology, 2010)

Cortical activation during cocaine use and extinction in rhesus monkeys - Leonard L. Howell; John R. Votaw; Mark M. Goodman; Kimberly P. Lindsey (Psychopharmacology, 2010)

Increased glutamate-stimulated release of dopamine in substantia nigra of a rat model for attention-deficit/hyperactivity disorder—lack of effect of methylphenidate - Fleur L. Warton; Fleur M. Howells; Vivienne A. Russell (Metabolic Brain Disease, 2009)

Behavioral and neurochemical effects of cocaine and diphenhydramine combinations in rhesus monkeys - Matthew L. Banks; Monica L. Andersen; Kevin S. Murnane; Rebecca C. Meyer; Leonard L. Howell (Psychopharmacology, 2009)

Role of dopamine transporters in the behavioral effects of 3,4-methylenedioxymethamphetamine (MDMA) in nonhuman primates - William E. Fantegrossi; Rayna M. Bauzo; Daniel M. Manvich; Jose C. Morales; John R. Votaw; Mark M. Goodman; Leonard L. Howell (Psychopharmacology, 2009)

Effects of cocaine self-administration history under limited and extended access conditions on in vivo striatal dopamine neurochemistry and acoustic startle in rhesus monkeys - Porche’ Kirkland Henry; Michael Davis; Leonard L. Howell (Psychopharmacology, 2009)

Cocaine-induced reinstatement during limited and extended drug access conditions in rhesus monkeys - Porche’ Kirkland Henry; Leonard L. Howell (Psychopharmacology, 2009)

Radiometric surface temperature calibration effects on satellite based evapotranspiration estimation - J. L. Chávez; P. H. Gowda; T. A. Howell; K. S. Copeland (International Journal of Remote Sensing, 2009)

High genetic differentiation and cross-shelf patterns of genetic diversity among Great Barrier Reef populations of Symbiodinium - E. J. Howells; M. J. H. van Oppen; B. L. Willis (Coral Reefs, 2009)

Remote sensing of contrasting tillage practices in the Texas Panhandle - Prasanna H. Gowda; T. A. Howell; S. R. Evett; J. L. Chavez; L. New (International Journal of Remote Sensing, 2008)

ET mapping for agricultural water management: present status and challenges - Prasanna H. Gowda; Jose L. Chavez; Paul D. Colaizzi; Steve R. Evett; Terry A. Howell; Judy A. Tolk (Irrigation Science, 2008)

Mapping of a gene (Vir) for a non-glaucous, viridescent phenotype in bread wheat derived from Triticum dicoccoides, and its association with yield variation - J. R. Simmonds; L. J. Fish; M. A. Leverington-Waite; Y. Wang; P. Howell; J. W. Snape (Euphytica, 2008)

Interoperability of Neuroscience Modeling Software: Current Status and Future Directions - Robert C. Cannon; Marc-Oliver Gewaltig; Padraig Gleeson; Upinder S. Bhalla; Hugo Cornelis; Michael L. Hines; Fredrick W. Howell; Eilif Muller; Joel R. Stiles; Stefan Wils; Erik De Schutter (Neuroinformatics, 2007)

Assessment of cognitive function in the heterozygous reeler mouse - Dilja D. Krueger; Jessica L. Howell; Britni F. Hebert; Peter Olausson; Jane R. Taylor; Angus C. Nairn (Psychopharmacology, 2006)

Gene Expression Patterns During Somatic Embryo Development and Germination in Maize Hi II Callus Cultures - Ping Che; Tanzy M. Love; Bronwyn R. Frame; Kan Wang; Alicia L. Carriquiry; Stephen H. Howell (Plant Molecular Biology, 2006)

Indole-3-carbinol-induced death in cancer cells involves EGFR downregulation and is exacerbated in a 3D environment - E. P. Moiseeva; L. H. Fox; L. M. Howells; L. A. F. Temple; M. M. Manson (Apoptosis, 2006)

Does the mitochondrial genome play a role in the etiology of Alzheimer’s disease? - Joanna L. Elson; Corinna Herrnstadt; Gwen Preston; Leon Thal; Christopher M. Morris; J. A. Edwardson; M. Flint Beal; Douglass M. Turnbull; Neil Howell (Human Genetics, 2006)

Development of the dopamine transporter selective RTI-336 as a pharmacotherapy for cocaine abuse - F. Ivy Carroll; James L. Howard; Leonard L. Howell; Barbara S. Fox; Michael J. Kuhar (The AAPS Journal, 2006)

Reproductive isolation among morphotypes of the Atlantic seastar species Zoroaster fulgens (Asteroidea: Echinodermata) - Kerry L. Howell; Alex D. Rogers; Paul A. Tyler; David S. M. Billett (Marine Biology, 2004)

Spatial, temporal and size-class variation in the diet of estuary perch (Macquaria colonorum) in the Hopkins River, Victoria, Australia - Timothy Howell; Laurie Jon Laurenson; Jackie H. Myers; Paul L. Jones (Hydrobiologia, 2004)

Functional imaging and neurochemical correlates of stimulant self-administration in primates - Leonard L. Howell; Kristin M. Wilcox (Psychopharmacology, 2002)

Cocaine-induced brain activation determined by positron emission tomography neuroimaging in conscious rhesus monkeys - Leonard L. Howell; John M. Hoffman; John R. Votaw; Alyson M. Landrum; Kristin M. Wilcox; Kimberly P. Lindsey (Psychopharmacology, 2002)

MUSCLE-DERIVED CD45−SCA-1+C-KIT− PROGENITOR CELLS GIVE RISE TO SKELETAL MUSCLE MYOTUBES IN VITRO - CASSANDRE L. ROYER; JONATHAN C. HOWELL; PAUL R. MORRISON; EDWARD F. SROUR; MERVIN C. YODER (In Vitro Cellular & Developmental Biology - Animal, 2002)

Cocaine-induced changes in extracellular dopamine determined by microdialysis in awake squirrel monkeys - P. W. Czoty; J.B. Justice Jr; L. L. Howell (Psychopharmacology, 2000)

An integrated AFLP and RFLP Brassica oleracea linkage map from two morphologically distinct doubled-haploid mapping populations - R. L. Sebastian; E. C. Howell; G. J. King; D. F. Marshall; M. J. Kearsey (Theoretical and Applied Genetics, 2000)

Mercury Concentrations in Louisiana and Chinese Crayfish - L. J. Schuler; J. P. Howell; M. G. Heagler (Bulletin of Environmental Contamination and Toxicology, 2000)

Metal Content Profiles in Mushrooms Collected in Primary Forests of Latin America - D. Michelot; F. Poirier; L. M. Melendez-Howell (Archives of Environmental Contamination and Toxicology, 1999)

The Student Watershed Research Project (SWRP): collecting watershed data for use by resource management agencies - Deborah J. Lev; Stacy L. Renfro; D. Torrey Lindbo; Wes Jarrell; Jane Blair; Steve Andrews; Lin Howell (Urban Ecosystems, 1998)

Effect of aluminum on cytoplasmic Ca 2+ homeostasis in root hairs of Arabidopsis thaliana (L.) - David L. Jones; Simon Gilroy; Paul B. Larsen; Stephen H. Howell; Leon V. Kochian (Planta, 1998)

Telemetry system for monitoring anterior cruciate ligament graft forcesin vivo - E. L. McKee; D. P. Lindsey; M. L. Hull; S. M. Howell (Medical & Biological Engineering & Computing, 1998)

Serotonergic modulation of the discriminative-stimulus effects of cocaine in squirrel monkeys - Kevin F. Schama; L. L. Howell; Larry D. Byrd (Psychopharmacology, 1997)

Pharmacological interactions between serotonin and dopamine on behavior in the squirrel monkey - L. L. Howell; Paul W. Czoty; Larry D. Byrd (Psychopharmacology, 1997)

Multiresolution Flux Decomposition - J. F. Howell; L. Mahrt (Boundary-Layer Meteorology, 1997)

Behavioral and physiological effects of xanthines in nonhuman primates - L. L. Howell; Vicki L. Coffin; Roger D. Spealman (Psychopharmacology, 1997)

Developmental patterns of 3-hydroxykynurenine accumulation in white and various other eye color mutants of Drosophila melanogaster - A. J. Howells; K. M. Summers; Rosemary L. Ryall (Biochemical Genetics, 1977)

The ommochrome biosynthetic pathway in Drosophila melanogaster: The head particulate phenoxazinone synthase and the developmental onset of xanthommatin synthesis - M. Yamamoto; A. J. Howells; Rosemary L. Ryall (Biochemical Genetics, 1976)

A biochemical study of the scarlet eye-color mutant of Drosophila melanogaster - A. J. Howells; Rosemary L. Ryall (Biochemical Genetics, 1975)

Notes on the biology of a spider parasiteColpomeria kincaidii Ashmead [Hymenoptera: Ichneumonidae] - J. O. Howell; R. L. Pienkowski (BioControl, 1972)